Penerapan Bimbingan Kelompok Berbasis Hadist Untuk Meningkatkan Kedisiplinan Dalam Melaksanakan Shalat Berjamaah Pada Penerima Manfaat Sentra “Budi Perkasa” Palembang - Ragil Lutfiani; Kusnadi Kusnadi; Zhila Jannati (Social Science and Contemporary Issues Journal, 2023)
Discipline in congregational prayer is very important so that each individual can obtain multiple rewards from Allah SWT. This research aims to determine the level of discipline in congregational prayers of beneficiaries (PM) before and after having hadith-based group guidance, as well as to determine the application of hadith-based group guidance in improving discipline in congregational prayers of beneficiaries. A qualitative approach with descriptive research methods was used by researchers in this research. 8 beneficiaries at the Palembang "Budi Perkasa" Center were selected to be research subjects. Data collection techniques in this research include observation, interviews and documentation. The activities in data analysis are in the form of data reduction, data presentation, and drawing conclusions. This research obtained the results, namely (1) There was still a low level of discipline in congregational prayers among beneficiaries at the "Budi Perkasa" Center in Palembang before the implementation of hadith-based group guidance where clients were still unable to comply with the applicable rules, could not arrange time according to schedule and had low prayer discipline. congregation and delaying congregational prayers. (2) The application of hadith-based group guidance to improve congregational prayer discipline among beneficiaries is carried out through 4 stages, namely the formation stage, transition stage, activity stage, and conclusion stage. This guidance was carried out in 5 meetings using 4 stages. It can be concluded that the problem of congregational prayer discipline among the beneficiaries has made some progress and has undergone changes. (3) There was an increase in discipline in carrying out congregational prayers among the beneficiaries of the Palembang "Budi Perkasa" Center after the implementation of hadith-based group guidance where clients were able to comply with applicable rules, could arrange time according to schedule and increased discipline in congregational prayers